If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(1 + -7n) = 0 (1 * 3 + -7n * 3) = 0 (3 + -21n) = 0 Solving 3 + -21n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -21n = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -21n = 0 + -3 -21n = 0 + -3 Combine like terms: 0 + -3 = -3 -21n = -3 Divide each side by '-21'. n = 0.1428571429 Simplifying n = 0.1428571429
| r-10=-12 | | x^2+3x=-4(-2x+1)-2 | | 12x-33=3x+75 | | -4.9x^2+9x+1.2=0 | | 2(2y-3)+3x=7 | | 0=2(2x^2-103x+546) | | 4x=x+5+2x-1 | | 4(j+5)=2 | | 13-2=j+6 | | -4(4a-8)= | | -4(4a-7)= | | Y=-12e^2x+36e^4x | | r+0.48=1.6 | | h(t)=-16x^2+85 | | 6(1)-(-7)=13 | | c/3+7=11/2 | | -(1+11n)= | | 6x+3x=1251 | | 5x+11=35 | | 2h+3.4forh=3 | | 5x-3=21-X | | x/2+2/7= | | -4-6m-m=2m-4 | | Y=7(x+870) | | 24x+4(x-2)=10(x+2)+8 | | -4(b-3)= | | 1.50h+9.99=36.99 | | Y+24=-14 | | 10+22xn=98 | | 18-4n=6-16m | | 2(4(5)-12)+3(5)= | | 6+x+3=4x+8 |